Maternal consumption of soy and isoflavones during pregnancy and risk of childhood behavioural problems: the Kyushu Okinawa Maternal and Child Health Study - Miyake, Yoshihiro; Tanaka, Keiko; Okubo, Hitomi; Sasaki, Satoshi; Tokinobu, Akiko; Arakawa, Masashi (International journal of food sciences and nutrition, 2021)
It is uncertain whether the effects of prenatal exposure to isoflavones on childhood behaviour are beneficial or detrimental. This prebirth cohort study investigated the associations between maternal consumption of soy products and isoflavones during pregnancy and behavioural problems in Japanese children aged 5 years. Subjects were 1199 mother-child pairs. Emotional problems, conduct problems, hyperactivity problems, peer problems and low prosocial behaviour were assessed using the Strengths and Difficulties Questionnaire. Maternal total soy product consumption during pregnancy was independently inversely associated with childhood hyperactivity and peer problems. Maternal fermented soybean consumption during pregnancy was independently inversely associated with childhood hyperactivity problems. Maternal isoflavone consumption during pregnancy was independently inversely related to childhood hyperactivity problems. Maternal consumption of total soy products, fermented soybean and isoflavones during pregnancy may be protective against hyperactivity problems in Japanese children. Also, maternal total soy product consumption during pregnancy may be preventive against childhood peer problems.